ANALISIS PROFITABILITAS USAHA TAHU PADA INDUSTRI TAHU AFIFAH DI KOTA PALU - Kadar, Darma; Antara, Made; Muis, Abdul (AGROTEKBIS, 2017)
The aim of this research is to know the income and the profitability business value in tofu industry âAfifahâ Palu City. This research already implemented started February until March 2016. The determination of respondent was done intentionally (purposive). The number of respondent taken as many as 10 people from 42 labor. Analysis result of income indicates that the average income acquired from tofu industry âAfifahâ during two-month Rp 52.606.058,5. Analysis result of profitability showed that the investment and capital issued for excellent gain produced that showed by ROI and ROE value increase from February to March 5,76% for each 7,35% and 10,87%, 16,18%.Â Key Words: Income, profitability, industry.